2009
DOI: 10.1158/1535-7163.mct-09-0396
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activation of the hypoxia-targeted cytotoxin AQ4N in human tumor xenografts

Abstract: AQ4N (banoxantrone) is a prodrug that, under hypoxic conditions, is enzymatically converted to a cytotoxic DNA-binding agent, AQ4. Incorporation of AQ4N into conventional chemoradiation protocols therefore targets both oxygenated and hypoxic regions of tumors, and potentially will increase the effectiveness of therapy. This current pharmacodynamic and efficacy study was designed to quantify tumor exposure to AQ4 following treatment with AQ4N, and to relate exposure to outcome of treatment. A single dose of 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…CI-1010 did not proceed to clinical trials because of the irreversible retinal toxicity observed in preclinical testing (21). HAPs that have advanced to clinical trials include tirapazamine (22,23), PR104 (24,25), AQ4N (26,27), and TH-302 (28)(29)(30)(31). TH-302 (1-methyl-2-nitro-1H-imidazole-5-yl) N, N 0 -bis (2-bromoethyl) diamidophosphate is a 2-nitroimidazole-linked prodrug of a brominated version of isophosphoramide mustard (Br-IPM; ref.…”
Section: Introductionmentioning
confidence: 99%
“…CI-1010 did not proceed to clinical trials because of the irreversible retinal toxicity observed in preclinical testing (21). HAPs that have advanced to clinical trials include tirapazamine (22,23), PR104 (24,25), AQ4N (26,27), and TH-302 (28)(29)(30)(31). TH-302 (1-methyl-2-nitro-1H-imidazole-5-yl) N, N 0 -bis (2-bromoethyl) diamidophosphate is a 2-nitroimidazole-linked prodrug of a brominated version of isophosphoramide mustard (Br-IPM; ref.…”
Section: Introductionmentioning
confidence: 99%
“…radiotherapy that target the proliferating cells, to destroy the cancer cells in hypoxic niches that are protected from cellular damage caused by free oxygen radicals [24]. AQ4N is a prodrug activated under hypoxic conditions to AQ4 which interferes with DNA replication by inhibiting topoisomerase II activity [25][26][27][28][29]. As a single-agent, administration of AQ4N is effective in the treatment of multiple types of pancreatic cancers in mice, controlling the primary tumour growth and spontaneous liver metastasis formation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the combination of AQ4N with antiangiogenesis that we propose might be more effective when applied to other bioreductive drugs, or in the case of AQ4N by treatment at a lower dose but at a greater frequency of administration or in combination with radiation (Lalani et al, 2007;Williams et al, 2009). We did not directly assay AQ4N penetration to the flank tumors, but we used pimonidazole staining to verify that hydralazine treatment increases tumor hypoxia significantly; this, in turn, is expected to increase tumor accumulation of AQ4, as has been shown in several tumor models (Atkinson et al, 2007;Albertella et al, 2008;Williams et al, 2009). In contrast to AQ4N, mitoxantrone has poor tumor penetration, but the combination of AQ4N with mitoxantrone can result in more effective antitumor activity due to AQ4N targeting hypoxic regions and mitoxantrone targeting less hypoxic regions (Tredan et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…AQ4N is considered an ideal bioreductive drug in that it penetrates deep into tumor tissue (Tredan et al, 2009). Its active metabolite, AQ4, is stable, localizes to hypoxic tumor regions in both preclinical and clinical studies (Albertella et al, 2008;Williams et al, 2009), and binds to DNA even under normoxic conditions, yet can passively diffuse into neighboring tumor cells (Smith et al, 1997). In contrast, poor tumor penetration is achieved with the related drug mitoxantrone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation